Design and Development of Simple Liquid Chromatographic Technique for the Rapid Determination of Ruxolitinib (RUXO) in Bulk Drugs along with Characterization of Forced Degradation Studies - Sahu, Sarangadhara; Panda, Susanta Kumar; Sahoo, Sudhir Kumar; Khandai, Madhusmruti; Prusty, Amaresh (Indian Journal of Pharmaceutical Education and Research)
Objectives: The motive behind this work is to develop a simple, rapid, accurate, and precise High-Performance Liquid Chromatography (HPLC) method for determining Ruxolitinib (RUXO) in bulk drugs and to study drug degradation behavior under various stress conditions as per International Council for Harmonization (ICH) guidelines. Materials and Methods: In this method, a Phenomenex ODS C-18 (250×4.6 mm, 5 µm) column was used by taking a mobile phase, which is methanol to acetonitrile, in the ratio of 60:40 v/v. pH is adjusted to 5.6 with acetic acid. A 1 mL/min flow rate was maintained, taking 25 µl as the injection volume. The eluted compounds were detected by a UV detector at a 254 nm wavelength at ambient temperature, with a 6 min run time. Results: The method shows a linear calibration curve in the concentration range of 10-70 μg/mL for the RUX with a regression coefficient of 0.999. Parameters were accessed by following the ICH (Q2R1) guideline. % Relative Standard Deviation (RSD) of precision was found to be 0.41, which is within the acceptance criteria. The Limit of Detection (LOD) value was found to be 1.5 µg/mL, and the Limit of Quantification (LOQ) is 4.5 µg/mL. The method was also utilized, developed, and validated for the estimation of drugs. Degradation tests were carried out at different conditions, like in acidic, basic, neutral, and oxidative conditions using H₂O₂. Photolytic and thermal degradation were performed at 60ºC in a hot air oven. Conclusion: The outcomes obtained after the stress testing reveal that the RUX drug substance is stable under various stress conditions, showing its accurate, precise, rapid analysis of RUXO and hence, its suitability for routine analysis in quality control laboratories for quantitative analysis of the drug.
Keywords: Ruxolitinib; HPLC; Method Development; Validation; Force Degradation Studies; ICH Guidelines